2014
DOI: 10.1016/j.jviromet.2013.08.035
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of rapid and simple techniques for the enrichment of viruses prior to metagenomic virus discovery

Abstract: The discovery of new or divergent viruses using metagenomics and high-throughput sequencing has become more commonplace. The preparation of a sample is known to have an effect on the representation of virus sequences within the metagenomic dataset yet comparatively little attention has been given to this. Physical enrichment techniques are often applied to samples to increase the number of viral sequences and therefore enhance the probability of detection. With the exception of virus ecology studies, there is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
180
3
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 186 publications
(190 citation statements)
references
References 34 publications
5
180
3
2
Order By: Relevance
“…Cultured virus isolates were used as a model system to demonstrate the HIV-SMART principle and the breadth of diversity it could accommodate. A preponderance of metagenomics papers describing new methods have also relied on cultured isolates or transfected plasmids with lower host backgrounds and higher virus titers (13,(29)(30)(31)(32)(33). However, sequencing directly from plasma is the most expedient workflow and reveals which replication-competent viruses are circulating in the patient.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Cultured virus isolates were used as a model system to demonstrate the HIV-SMART principle and the breadth of diversity it could accommodate. A preponderance of metagenomics papers describing new methods have also relied on cultured isolates or transfected plasmids with lower host backgrounds and higher virus titers (13,(29)(30)(31)(32)(33). However, sequencing directly from plasma is the most expedient workflow and reveals which replication-competent viruses are circulating in the patient.…”
Section: Discussionmentioning
confidence: 99%
“…We optimized the protocol for this purpose and found that the addition of benzonase prior to extraction increased HIV-1 reads (ϳ10-to 50-fold) and genome coverage (from 28% to 54%), presumably by decreasing human background nucleic acid, while a postextraction DNase treatment was often detrimental ( Fig. 3; see Table S2 in the supplemental material) (24,30). The selection of nucleic acid extraction method also drove performance, with higher HIV-1 RNA recovery correlating with higher genome coverage.…”
Section: Discussionmentioning
confidence: 99%
“…Ticks were pooled prior to nucleic acid extraction; two pools of I. scapularis (n ϭ 30/pool), two pools of D. variabilis (n ϭ 30/pool), and a single pool of A. americanum (n ϭ 25) were prepared. A two-step purification and nuclease treatment protocol was followed prior to extraction to enrich for viral sequences and minimize host, bacterial, and fungal templates that could compete with the virus template in HTS (22). Each tick pool was homogenized in 500 l of phosphate-buffered saline (PBS), followed by purification through a 0.45-m filter.…”
Section: Methodsmentioning
confidence: 99%
“…Viral nucleic acid enrichment was performed by a combination of centrifugation (10 min at 6,000 x g), filtration (at 0.45 μm) and nuclease treatment using 0.1 U μL − 1 Turbo DNAse (Life Technologies) as described before [16]. Nucleic acid extraction was then performed with a NucliSens easyMAG magnetic bead system (BioMérieux).…”
Section: Metagenomic Sequencing and De Novo Assembly Of Consensus Seqmentioning
confidence: 99%